2022
DOI: 10.1002/jat.4310
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation on the toxic effect of silver (Ag) and zinc oxide (ZnO) nanoparticles on different trophic levels in aquatic ecosystems: A review

Abstract: Silver (Ag) and zinc oxide (ZnO) are considered to be harmful nanoparticles (NPs) to the aquatic organisms as their intake causes toxic impacts to wildlife, through direct ingestion or by the transference along trophic levels. Over usage and ultimate disposal of metallic particles from the industries subsequently lead to pollution of the aquatic environment. Exposure of NPs in aquatic ecosystem alters biological and physicochemical parameters of the water and aquatic organisms and determines their potential ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…On the other hand, Sibiya et al (2022) concluded that the presence of ZnO‐NPs in aquatic systems can cause adverse influences such as alterations to the organism's oxidative status, metabolic capacity, antioxidant defense system, reproductive performance, growth, maturation rate, and development. In the present study, adverse ZnO effects increased with increasing time for all zinc forms after the fourth week of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Sibiya et al (2022) concluded that the presence of ZnO‐NPs in aquatic systems can cause adverse influences such as alterations to the organism's oxidative status, metabolic capacity, antioxidant defense system, reproductive performance, growth, maturation rate, and development. In the present study, adverse ZnO effects increased with increasing time for all zinc forms after the fourth week of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, the fate of nanomaterials in waters or other media can be critical, being particularly harmful also in combination with additional pollutants such as microplastics …”
Section: Conclusion: Open Issues and Challengesmentioning
confidence: 99%
“…As mentioned, the fate of nanomaterials in waters 297 or other media can be critical, being particularly harmful also in combination with additional pollutants such as microplastics. 298 The preparation of ZnO NS formulations with known and controlled size, surface charge, and shell composition should be regarded as the Holy Grail for proper evaluation of cytotoxic and adverse effects.…”
Section: Conclusion: Open Issues and Challengesmentioning
confidence: 99%
“…While most AgNPs are removed by sludge adsorption or chlorine precipitation in sewage treatment plants [ 24 ], unremoved AgNPs in wastewater can undergo oxidization, resulting in the generation of toxic Ag ions (Ag + ), which have certain detrimental eco-environmental consequences, such as exerting harm to aquatic organisms [ [25] , [26] , [27] ]. Furthermore, AgNPs can be transformed into low-solubility salts such as silver chloride (AgCl) and silver sulfide (Ag 2 S) [ 24 , 28 , 29 ], which can accumulate via the food chain [ 24 , 30 ], and harm a wide range of organisms [ [31] , [32] , [33] ], including vulnerable populations such as elders and pregnant women. Embryos, fetuses, and infants lack a well-developed defense system, making them more susceptible to xenobiotics [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%